O10. Optimism or Greed: Methods of dose escalation in IGABT through total dose constraint optimization. (September 2016) - van der Walt, H.; Shaw, W.
Abstract : Introduction: Image Guided Adaptive Brachytherapy (IGABT) is long overdue in replacing traditional 2D brachytherapy approaches. The key advantage of IGABT is conforming and optimizing dose to the anatomy of the individual patient, considering tumour volume, topography and organs at risk (OARs) on the treatment day. OARs experience inter-fractional variations in volume, geometry and position in relation to tumour volumes. These variations ensure that some of the fractional OAR constraints may be reached in one fraction, but not necessarily in the remaining fractions. Exploitation of these variations through 'fractionation compensation' allows tumour dose escalation by optimizing fractional OAR dose constraints during the course of treatment and maintaining total dose constraints. Materials and methods: An in-house software module for IGABT treatment planning was developed to test two methods of tumour dose escalation. CT data sets of 10 cervix cancer patients receiving 5 high dose rate brachytherapy treatment fractions were used in the study. Manual optimization based on dose volume histogram (DVH) parameter and equivalent uniform dose (EUD) parameter was performed for all patients. Optimization was performed via fractionation compensation (total dose constraint optimization) in two schemes: 'Optimistic' and 'Greedy'. Optimistic equally distributes the compensation in the remaining undelivered fractions, while Greedy integrates the entire compensation into the current fraction. Results: DVH-based optimization resulted in an average tumour D90 of 91.2 Gy and 91.3 Gy for the optimistic and greedy schemes, respectively. EUD-based optimization resulted in 2.8% lower D90 values of 88.7 Gy and 88.8 Gy, respectively, with a reduction in OAR DVH parameters. Conclusion: We found no statistically significant difference between the fractionation compensation schemes. However, Greedy resulted in some additional dose escalation for individuals. Both planning approaches reached the tumour dose objectives, while EUD planning resulted in lower OAR DVH parameters.